2014
DOI: 10.1371/journal.pone.0114024
|View full text |Cite|
|
Sign up to set email alerts
|

Repeated Exposure of Adult Rats to Transient Oxidative Stress Induces Various Long-Lasting Alterations in Cognitive and Behavioral Functions

Abstract: Exposure of neonates to oxidative stress may increase the risk of psychiatric disorders such as schizophrenia in adulthood. However, the effects of moderate oxidative stress on the adult brain are not completely understood. To address this issue, we systemically administrated 2-cyclohexen-1-one (CHX) to adult rats to transiently reduce glutathione levels. Repeated administration of CHX did not affect the acquisition or motivation of an appetitive instrumental behavior (lever pressing) rewarded by a food outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 65 publications
0
10
0
1
Order By: Relevance
“…G. jasminoides Ellis, one of the other component of JYCF has exerted an ability to increase the concentration of NE and 5-HT in CUMS rat hippocampus[ 38 , 39 ]. In addition, research has shown that chronic stress could increase the reactive oxygen species generation (ROS) in several brain areas and regulate mood [ 40 , 41 ]. Forsythia suspense, one of the components of JYCF, had been reported to have the ability to prevent ROS generation, which may contribute to the etiology and progression of major depression [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…G. jasminoides Ellis, one of the other component of JYCF has exerted an ability to increase the concentration of NE and 5-HT in CUMS rat hippocampus[ 38 , 39 ]. In addition, research has shown that chronic stress could increase the reactive oxygen species generation (ROS) in several brain areas and regulate mood [ 40 , 41 ]. Forsythia suspense, one of the components of JYCF, had been reported to have the ability to prevent ROS generation, which may contribute to the etiology and progression of major depression [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…41 Inversely, glutathione depletion in rats leads to SZ-like phenotypes. 42 , 43 , 44 In addition, knockout mice that lack a crucial subunit of the GCL enzyme show significant reduction of glutathione levels in the anterior cortex, 45 especially during the prepuberal period, which is followed by SZ-like behaviour in the time frame of disease onset 46 and SZ-like neural changes in the hippocampus (HIP) of the adult knockout mice, including an increase in oxidative stress and a decrease in the number of parvalbumin (PV) interneurons. 47 Therefore, redox imbalance may represent the main trigger for brain alterations before disease onset, which negatively influence cognition later on.…”
Section: Sz Is Associated With Redox Imbalancementioning
confidence: 99%
“…It is important to highlight that induction of oxidative stress even with a transient increase can promote systemic effects, including dementia, Alzheimer's and Parkinson's disease, 83 and variations in behavioral and cognitive function. 84 Furthermore, the elevated levels of lipid peroxidation products are associated with atherosclerosis 85 and kidney disease. 86 Therefore, considering the fact that only a few investigations have been performed to assess the systemic effect of endodontic sealers, it is clear that further studies are necessary to elucidate their possible toxic effects, as this relationship is not yet completely understood.…”
Section: Systemic Conditions and Their Relationships With Dental Matementioning
confidence: 99%